Effects of microencapsulated phytonutrients from fruit peel pellet on rumen fermentation efficiency, degradability, methane production and microbial diversity - Sukruthai Sommai; Chanon Suntara; Maharach Matra; Srisan Phupaboon; Gamonmas Dagaew; Chaichana Suriyapha; Rittikeard Prachumchai; Metha Wanapat (Animal Bioscience)
Objective The current study aimed to determine the impact of supplementing fruit peel pellet microencapsulated phytonutrients (mMARABAC) on rumen fermentation efficiency, in vitro degradability, methane production, and microbial diversity. Methods The experiment was completely random, and the dietary treatments were mMARABAC supplements at 0, 5, 10, and 15 mg/500 mg dry matter (DM) of substrate (rice straw and concentrate). Results The experiment’s results demonstrated that mMARABAC supplementation significantly affected the gas production from the insoluble fraction (b), rate of gas production value (c), and potential extent of gas (|a|+b) value (p<0.05), while the soluble fraction of gas production (a) was not influenced by the treatments. Furthermore, mMARABAC increased the cumulative gas at 96 h after incubation (p<0.05) when mMARABAC was supplemented with 5 mg of total DM substrate. However, mMARABAC supplementation did not have an effect on in vitro degradability of dry matter (p>0.05). The supplementation of mMARABAC did not significantly affect ruminal pH and NH3-N (p>0.05). Additionally, there was linearly (p<0.05) decreased CH4 production at 24 hours of incubation. The mMARABAC supplementation to the diet did not affect the concentration of total volatile fatty acids, acetic acid (C2), propionic acid (C3), butyric acid, or the C2:C3 ratio (p>0.05). The effect of mMARABAC supplementation on Fibrobacter succinogenes, Ruminococcus albus, Ruminococcus flavefaciens, Butyrivibrio fibrisolvens and Megasphaera elsdenii was different between treatments (p<0.05), while the mMARABAC supplement had an effect on Methanobacterial (p>0.05). Conclusion This study suggested that ruminants could use agricultural by-products as a source of phytonutrients by supplementing with mMARABAC at 5 mg/500 mg DM of substrate.